'Eaten by the sea': human rights claims for the impacts of climate change upon remote subnational communities. Issue 2 (September 2018) - Cullen, Miriam
Abstract : The low-lying islands and atolls of the Pacific have been among the first places to experience the most severe impacts of anthropogenic climate change. Some of the affected islands are nation-states possessing the capacity to negotiate treaties and to directly participate in international forums such as the United Nations (UN). Others, however, are subnational jurisdictions, made up of people who live remote from the governing majority and yet are extremely vulnerable to national policy decisions, especially when it comes to climate change and its impacts. This article examines one potential avenue for redress for minority populations living in remote subnational jurisdictions where national policy on climate change arguably compromises their human rights: a communication to the UN Human Rights Committee (HRC). The article takes as its primary case study the people of the Torres Strait Islands, which form part of the state of Australia.